Carbon and energy metabolism for the mixotrophic culture of Chlorella vulgaris using sodium acetate as a carbon source - Yan, Xi; Shan, Shengzhou; Li, Xiaohui; Xu, Qingshan; Yan, Xiaojun; Ruan, Roger; Cheng, Pengfei (Frontiers in Microbiology, 2024)
There has been an emergence of a diversity of microalgal mixotrophic synergistic mechanisms due to substrate differences. In this study, the effects of the mixotrophic culture of Chlorella vulgaris were examined. The maximum values of cell density, specific growth rate, and cell dry weight of Chlorella vulgaris were 3.52*10 7 cells/mL, 0.75 d -1 , and 3.48 g/L in the mixotrophic mode, respectively. These were higher than the corresponding values of photoautotrophic or heterotrophic modes. Moreover, it was found that the concentrations of sodium bicarbonate consumed by the Chlorella vulgaris under mixotrophic and photoautotrophic modes were 635 mg/L/d and 505 mg/L/d, respectively; the concentrations of sodium acetate consumed by the Chlorella vulgaris under mixotrophic and heterotrophic modes were 614 mg/L/d and 645 mg/L/d, respectively. The activity of Rubisco was 9.36 U/mL in the mixotrophic culture, which was 3.09 and 4.85 times higher than that of the photoautotrophic and heterotrophic modes, respectively. This indicated that the differences for the carbon source absorption efficiency of Chlorella vulgaris in the mixotrophy led to different internal metabolic efficiencies when compared to photoautotroph or heterotrophy. Additionally, Chlorella vulgaris exhibits a more rapid energy metabolism efficiency when operating in the mixotrophic mode.